IbM KELOMPOK WANITA TANI BABATAN APLIKASI BOKHASI PLUS UNTUK BUDIDAYA CABE - Nurlianti Nurlianti; Prihanani Prihanani (Universitas Bengkulu, 2018)
Problems faced by the group of partners as producers of bokhasi intend to improve the quality of the product that is improving the quality of bokhasi nutrient content and quality of product packaging. Bokhasi products so far will be upgraded to bokhasi plus by means of enrichment to produce bokhasi products with high nutrient content. Improving the quality of packing that was originally packed with used sacks will be enhanced to be a more attractive bokhasi packaging with the letters of hosi composition. Another problem is the desire of group members to obtain additional income beyond the main income as a palm oil planters by way of cultivation of chili plants by utilizing bokhasi plus as fertilizer because chili commodity has a promising sale value. The ultimate goal of both programs for both partners is to earn additional income from the cultivation of pepper plants and as a bokhasi plus producer apart from its main income of palm oil production. Benefits of activities that will be perceived by Partner One are able to be a stable and sustainable bokhasi plus producer with more quality products and packaging. Benefit for Partners Two after attending this program is able to become a producer of chili to get additional income other than its main income from the cultivation of palm. The main output of this program is the additional articles and outcomes of products as a tangible form of sustainable economic productive endeavors from both Partners. The first partner is the production of bokhasi plus the interesting packaging with the content of nutrient. The second partner is expected to all members of the women's group of farmers get additional income from chili cultivation. Keywords: bokhasi plus application, packaging, chili cultivation